2021
DOI: 10.1101/2021.06.03.21258001
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of the Mental Health Symptoms during the Covid-19 Pandemic in Southeast Asia

Abstract: Aims: The Covid-19 pandemic has had a substantial impact on the mental health of the general public and high-risk groups across the globe. Southeast Asia, one of the first regions to be affected by the outbreak, is of particular interest given its proximity and close links to China, experience with recent epidemics (i.e. SARS), and the variable course of the outbreak in the region thus far. The aim of this study was to systemically review and assess the prevalence of anxiety, depression and insomnia symptoms i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 65 publications
(100 reference statements)
2
20
0
Order By: Relevance
“…South-Eastern Asia showed the lowest prevalence of anxiety (6.6% to 49.6%) and depression (6.3% to 41%) but was unknown for insomnia since no data were available to review. A meta-analysis showed that the pooled prevalence of anxiety and depression in South-Eastern Asia was 22% and 16%, respectively [108]. Southern Asia had the lowest prevalence of insomnia (18.6% to 41.3%) and PTSD (2.1% to 7.3%) which was similar in a previous study [100].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…South-Eastern Asia showed the lowest prevalence of anxiety (6.6% to 49.6%) and depression (6.3% to 41%) but was unknown for insomnia since no data were available to review. A meta-analysis showed that the pooled prevalence of anxiety and depression in South-Eastern Asia was 22% and 16%, respectively [108]. Southern Asia had the lowest prevalence of insomnia (18.6% to 41.3%) and PTSD (2.1% to 7.3%) which was similar in a previous study [100].…”
Section: Discussionsupporting
confidence: 81%
“…This review proved that female healthcare providers showed a higher prevalence of all psychological impacts than males. A few reviews also showed similar findings [108,113,114]. The recommendation to include a gender perspective in the planning and designing support measures and intervention was widely documented.…”
Section: Discussionmentioning
confidence: 79%
“…The search generated 10 meta-analyses on mental health symptoms during COVID-19 from the six regions (Africa, Eastern Europe, Latin America South, and Asia and Southeast Asia nested within Asia) and four countries (China, Egypt, India, and Spain), as summarized in Table 1 (Chen et al, 2021 ; Chen, et al, In Press ; Chen et al, 2021 ; El-Qushayri et al, 2021 ; Hossain et al, 2021 ; Norhayati MY & Azman, 2021 ; Pappa, et al, in press ; Singh, Bajpai, & Kaswan, 2021 ; Zhang et al, 2021 ; Zhang et al, 2021 ). Table 1 tabulates these meta-analytical studies for easy comparisons.…”
Section: Resultsmentioning
confidence: 99%
“…Fourth, future research is encouraged to research the fear of failure and the IP model by considering the COVID-19 phenomenon. COVID-19 has been last for 2 years which is associated with businesses risks ( Yue et al, 2020 ; Li et al, 2021 ) and mental health symptoms, i.e., a high prevalence of anxiety, depression, and insomnia ( Chen et al, 2021 ; Pappa et al, 2021 ; Zhang et al, 2022 ). Although COVID-19 has reached researchers’ attention on IB policy ( Van Assche and Lundan, 2020 ) and strategy ( Verbeke and Yuan, 2021 ), there is no IB empirical research that explored the fear of failure.…”
Section: Implication For Future Researchmentioning
confidence: 99%
“…Globalisation of the world economy has created international opportunities. Nevertheless, taking the current international business (IB) environment into consideration, the global infection status of Coronavirus Disease-19 (COVID-19) had brought risks on economic activities ( Yue et al, 2020 ) and mental health disorders to individuals ( Chen et al, 2021 ; Pappa et al, 2021 ; Zhang et al, 2022 ). Internationalisation is instrumental to a firm’s survival and growth along with the potential for a positive effect on economic development ( The World Bank, 2019 ).…”
Section: Introductionmentioning
confidence: 99%